Safranal Inhibits Angiogenesis via Targeting HIF-1α/VEGF Machinery: In Vitro and Ex Vivo Insights - Abdalla, Ali; Murali, Chandraprabha; Amin, Amr (Frontiers in Oncology, 2022)
Nature has a nearly infinite inventory of unexplored phytochemicals and biomolecules that have the potential to treat a variety of diseases. Safranal exhibits anti-cancer properties and the present study explores its antiangiogenic property. Hepatocellular carcinoma (HCC) ranks as the sixth deadliest among all cancer types. Targeting the non-tumor vasculature supporting system is very promising as it has less plasticity, unlike malignant cells that are often associated with issues like drug resistance, poor prognosis, and relapse. In this study, we successfully inhibited the proliferation of primary human umbilical vein endothelial cells (HUVEC) with an IC50 of 300M and blocked VEGF secretion in HepG2 cells. Furthermore, safranal inhibited VEGF-induced angiogenesis in vitro and ex vivo via scratch wound assay, tube formation assay, transmembrane assay, and aortic ring assay. In addition, safranal downregulated the in vitro expression of HIF-1α, VEGF, VEGFR2, p-AKT, p-ERK1/2, MMP9, p-FAK, and p-STAT3. The present study is the first to reveal the antiangiogenic potential of safranal and propose its possible underlying mechanism in HCC.